Analisis Angka Kejadian Penyakit Infeksi Menular Seksual - Abubakar Betan; Rahmat Pannyiwi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; Sexually transmitted diseases are the most common infectious diseases and health problems that are currently getting a lot of attention because the incidence of STDs tends to continue to increase. Method; quantitative research used a descriptive-analytical method with cross-sectional study design. Data analysis used univariate and bivariate analysis using the chi-square statistical test. Results: statistical test of knowledge (p = 0.009), behavior (p = 0.009), and socioeconomic (p = 0.169) with the incidence of sexually transmitted infections. Conclusion; there is a relationship between knowledge and behavior and there is no socio-economic relationship with the incidence of sexually transmitted diseases.